2001
DOI: 10.1002/1521-2254(200101/02)3:1<3::aid-jgm167>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for hemophilia

Abstract: Hemophilia A and B are X-chromosome linked recessive bleeding disorders that result from a deficiency in factor VIII (FVIII) and factor IX (FIX) respectively. Though factor substitution therapy has greatly improved the lives of hemophiliac patients, there are still limitations to the current treatment that have triggered interest in alternative treatments by gene therapy. Significant progress has recently been made in the development of gene therapy for the treatment of hemophilia A and B. These advances paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 177 publications
1
14
0
Order By: Relevance
“…The skeletal muscle is a good platform for the expression of a therapeutic gene [1,2], such as a gene encoding a clotting factor [3], erythropoietin [4,5], or a hormone [6]. The systemic distribution of the transgene product from the skeletal muscle could compensate the insufficiency of the factor in the patient.…”
Section: Introductionsupporting
confidence: 89%
“…The skeletal muscle is a good platform for the expression of a therapeutic gene [1,2], such as a gene encoding a clotting factor [3], erythropoietin [4,5], or a hormone [6]. The systemic distribution of the transgene product from the skeletal muscle could compensate the insufficiency of the factor in the patient.…”
Section: Introductionsupporting
confidence: 89%
“…3,42 As FVIII and FIX proteins are naturally generated by liver sinusoidal endothelial cells (LSECs) and hepatocytes, respectively, the liver is an obvious target organ for gene therapy for haemophilia. 3,42 As FVIII and FIX proteins are naturally generated by liver sinusoidal endothelial cells (LSECs) and hepatocytes, respectively, the liver is an obvious target organ for gene therapy for haemophilia.…”
Section: Target Cells For Haemophilia Gene Therapymentioning
confidence: 99%
“…There are several different cell types that are attractive targets to treat haemophilia by gene therapy. 3,42 As FVIII and FIX proteins are naturally generated by liver sinusoidal endothelial cells (LSECs) and hepatocytes, respectively, the liver is an obvious target organ for gene therapy for haemophilia. Both viral and nonviral gene therapy systems targeting LSECs and hepatocytes have been explored.…”
Section: Target Cells For Haemophilia Gene Therapymentioning
confidence: 99%
“…Since that time, two additional clinical studies targeting haemophilia A and two human studies targeting haemophilia B have been initiated [2]. At present, none of the studies has convincingly demonstrated that they hold the key to a cure for either form of haemophilia, yet encouraging signs and substantial evidence have come out of these trials, as well as from related research, which support the optimistic view that gene therapy does indeed hold the key to a cure for haemophilia [3–6].…”
Section: Introductionmentioning
confidence: 99%